Practical data communications - Freeman, Roger L (Wiley Series in telecommunications and signal processing., 1995)
With the accelerating growth in the use of computers and PCs in the workplace, the practical aspects of designing and operating data communications systems have become increasingly more complex. Practical Data Communications provides the needed background and fills in the gaps for the many who must tackle this vital technology with little basic training. It does so in clear and precise terms and with a hands-on approach to network design and management aimed at ensuring the optimal implementation of data communications.